EVALUATING INTERNAL CSR USING IMPORTANCE AND PERFORMANCE ANALYSIS AT PT. MEARES SOPUTAN MINING - Gabriel Sepnatali Honief Tuilan; James D. D. Massie; Regina T. Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The purpose of this research is to evaluating internal CSR using importance and performance analysis at PT. Meares Soputan Mining. This research used quantitative method. 31 samples were collected with questionnaire distributed to the employee of PT. Meares Soputan Mining. The result of this research shows that the importance and performance of internal CSR refers to the actions that corporations choose to take to satisfy the expectations of employees, actively fulﬁll and improve organizational fairness regarding employees (such as improving the happiness and satisfaction of employees’ health), and ensure work safety and the growth and development of employees and 5 points Likert scale was used to help the data analysis in this research for importance and performance.